World Rowing Covid-19 pandemic. Return to training. Advice for post-peak and post-pandemic period. - Wilson, Fiona (Fédération Internationale des Sociétés d’Aviron, 2020)
The Coronavirus pandemic continues to evolve and is in different stages in different parts of the world. Within a country there might be areas in a peak phase with high risk of transmission close to others in which the situation may be even post-pandemic or normal.Therefore, the response to the pandemic is evolving differently across the world, in terms of governmental guidelines, the severity of the impact of COVID19 on different national populations. Therefore, given the present status, the FISA SMC advice from 27 February 2020 (for the spreading period) and 25 March 2020 (for the Peak period) has been updated to reflect the evolving global health situation.These guidelines cannot replace the priority provisions of the state governments and the locally responsible health authorities, but serve as a rowing-specific technical contribution.
Keywords: Rowing; Training; COVID-19